Bacteria for the degradation and modification of fats, oils, and grease. - Abdullah, Norhafizah; Abd Shukor, Mohd Yunus; Ahmadun, Fakhru'l-Razi; Shamaan, Nor Aripin (2010)
The invention discloses several Gram-positive microorganisms that effectively and efficently degrade fats, oils and grease. A composition comprising said microorganism and a degrading fatty acids and grease are also disclosed.